NOVEL MANGIFERIN-INFUSED PHYTOSOMAL GEL FOR WOUND HEALING: DEVELOPMENT, CHARACTERIZATION AND IN VIVO ASSESSMENT - Someshwar D. Mankara
Wound healing impairment remains a significant healthcare challenge. This study aimed to develop and evaluate a mangiferin-enriched phytosomal gel formulation to enhance wound healing through improved bioavailability and controlled release. The gel was developed using factorial design with varying concentrations of polymers and characterized through spectroscopic, thermal and microscopic analyses. The optimized formulation showed a particle size of 171.2 nm with high stability and drug entrapment of 87.35%. The gel maintained consistent drug release over 10 h, reaching 93.04% release, and remained stable for six months under accelerated conditions. Animal studies demonstrated superior wound healing efficacy, achieving 97.43% wound contraction after 14 days, compared to 48.21% in the control group. The findings indicate that the mangiferin-enriched phytosomal gel offers an effective solution for enhanced wound healing through improved bioavailability and controlled release properties.